Local site effect on seismic response of coupled transmission tower-line system - Bai, F.; Li, H.; Hao, Hong (2010)
The collapses of transmission towers in large earthquakes were partially caused by the pulling forces from the transmission lines generated from out-of-phase responses of the adjacent towers owing to nonuniform ground motions. A three-dimensional finite element model of transmission tower-line system is established, the nonlinear responses of the structural system at uneven sites are analysed subjected to spatially varying ground motions, and the local site effect due to different soil condition sets on structural response is mainly studied. The spatially varying ground motions are simulated stochastically based on an empirical coherency loss function and a filtered Tajimi-Kanai power spectral density function. The site effect is considered by a transfer function derived from one dimensional wave propagation theory. Compared with structural responses calculated using the uniform sites assumption, numerical results indicate that seismic responses of transmission towers and power lines are amplified when considering the local site effects. Therefore, in order to ensure the seismic safety of transmission tower-line system, an accurate estimation of the site conditions where the structural system located is essential. © 2010 ASCE.